2021
DOI: 10.1177/03000605211024875
|View full text |Cite
|
Sign up to set email alerts
|

High-dose short-course oral corticosteroid protocol for treatment of primary frozen shoulder: a retrospective cohort study

Abstract: Objective To evaluate the effect of high-dose prednisolone on the functional outcome of patients with early-stage primary frozen shoulder. Methods Eighteen patients treated with oral prednisolone at an initial dose of 1 mg/kg/day for primary frozen shoulder were retrospectively evaluated. The patients’ range of motion, Disabilities of the Arm, Shoulder, and Hand (DASH) score, Constant–Murley score, American Shoulder and Elbow Surgeons (ASES) score, and visual analog scale score were recorded at baseline and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, in the frozen stage, CHL thickness correlates negatively with the Er and Ir ranges of the shoulder ( 14 ), and FS patients with thickening of the CHL do not achieve good improvement of shoulder ROM using this method alone ( 24 ). Many studies have shown that steroid drugs can effectively control pain associated with FS ( 25 ), but these drugs are relatively short acting ( 26 , 27 ). Traditional or single US-guided injection therapy is not the best method to treat FS, especially for patients in the frozen stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the frozen stage, CHL thickness correlates negatively with the Er and Ir ranges of the shoulder ( 14 ), and FS patients with thickening of the CHL do not achieve good improvement of shoulder ROM using this method alone ( 24 ). Many studies have shown that steroid drugs can effectively control pain associated with FS ( 25 ), but these drugs are relatively short acting ( 26 , 27 ). Traditional or single US-guided injection therapy is not the best method to treat FS, especially for patients in the frozen stage.…”
Section: Discussionmentioning
confidence: 99%